AMY’S CHARACTER IN THE MOVIE “GONE GIRL” - Elfryda, Natalia; Rosyidin, Iskandar; Sari, Dewi Purnama (Direktorat Riset dan Pengabdian kepada Masyarakat, Universitas Bina Darma, 2018)
In this paper, the researcher wanted to find out the factors of Amy?s mental disorder, how Amy?s character and what effect of mental disorder to the movie. The method of data analysis was descriptive, because the researcher explained and interpreted the data from the action of Amy in the movie. The books of literary theories were used to understand the theory that was relevant to this research. The approach used in this research was psychological of anxiety approach to identify the factors of Amy?s mental disorder in describing Amy?s character. The result of this analysis showed that there were three types of anxiety as the factors of Amy?s mental problems in this movie, realistic, moral, and neurotic anxiety. She experienced anxieties because of her husband that caused Amy had a mental disorder. Amy was described as an antagonist, cruel, manipulative, liar, psychopath, and antisocial. The effect of mental disorder to the movie was the story had different atmosphere and made the story more complicated.